2006
DOI: 10.1080/02701367.2006.10599356
|View full text |Cite
|
Sign up to set email alerts
|

“...If I Had a Choice, I Would....” A Feminist Poststructuralist Perspective on Girls in Physical Education

Abstract: A significant number of studies evidence girls' lack of participation in physical education. This study used feminist poststructuralism to examine the ways in which high school girls participated in or resisted physical education. Using qualitative research methods, researchers collected field notes, informal interviews, and formal interviews with the teacher and 15 female students. In contrast to previous studies, girls in this study enjoyed and valued physical activity. As active agents, they chose to partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
82
0
20

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 18 publications
2
82
0
20
Order By: Relevance
“…Accordingly, the present study examined the relationship between the nature of traditional games proposed by a teacher and the emotional responses of participating students. Understanding this relationship could allow teachers to structure the content of games so as to produce different (positive or negative) kinds of experience (Azzarito, Solmon, & Harrison, 2006). In addition, this kind of information could enable physical education teachers to help students develop the attitudes, behaviors, and cognitive strategies required to become "healthy and competent" overall-that is, socially, emotionally, academically, and physically, because these four domains are closely related to one another (Bailey et al, 2009).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly, the present study examined the relationship between the nature of traditional games proposed by a teacher and the emotional responses of participating students. Understanding this relationship could allow teachers to structure the content of games so as to produce different (positive or negative) kinds of experience (Azzarito, Solmon, & Harrison, 2006). In addition, this kind of information could enable physical education teachers to help students develop the attitudes, behaviors, and cognitive strategies required to become "healthy and competent" overall-that is, socially, emotionally, academically, and physically, because these four domains are closely related to one another (Bailey et al, 2009).…”
mentioning
confidence: 98%
“…When the source of this uncertainty is based on the motor communication that takes place between players, four different motor domains can be established: (a) the psychomotor domain, in which the participant performs the task alone without any motor communication with others, as in a long-jump competition or when playing with a yo-yo; (b) the cooperative domain, in which participants share a common language involving clear messages of assistance, as in a children's ring-dancing game or a piggyback race; (c) the opposition domain, in which participants share a language of confusing signs, of messages that hide their true intentions, thereby enabling them to deceive their adversary, as in the case of arm wrestling or escaping from your pursuer in the game of tag; and (d) the cooperation-opposition domain, characteristic of those traditional games that combine opposition between rivals with collaboration among teammates, as in dodgeball or red rover, all of which are situations where motor communication must be transparent for teammates but opaque for rivals. The participants who are immersed in a given motor activity will evaluate each game situation according to their expectations (Azzarito et al, 2006;Collard, Oboeuf, & Ahmaidi, 2007;Greene & DeBacker, 2004;Puig & Vilanova, 2011), and the emotions they experience will depend on the evaluation they make at any given moment (Garcia Bengoechea, Sabiston, Ahmed, & Farnoush, 2010;Hatfield, Cacipoppo, & Rapson, 1994;Puig & Vilanova, 2011). Therefore, by considering the presence or not of a competitive element and the possible social relationships involved, we can classify motor games according to eight potential categories and thereby examine in greater detail the effect they produce on the emotional experience of participants.…”
mentioning
confidence: 99%
“…These goals allowed the teachers to believe physical education could be an equal-opportunity environment where competitive activities were embraced by boys and girls. But even in this environment, Azzaritto et al (2006) found that, girls were likely to be in a "subordinate" position in activities they perceived as for boys, such as basketball or flag football. To remain in active participation, girls have to "negotiate" to overcome the gender barriers in the learning space dominated by the masculine discourse.…”
Section: Introductionmentioning
confidence: 88%
“…Another salient tenet of gender issue in physical education is that despite perceived gender-appropriateness and perceived favoritism of content for males, female students refused to be sidelined in physical education (Azzaritto, Solmon, & Harrison, 2006). Qualitative data from the study suggested that parallel goals of having fun and learning in physical education kept both boys and girls from the influence of initial gendered-endorsement of activity choices.…”
Section: Introductionmentioning
confidence: 97%
“…However, there is evidence that the portrayal of girls as inactive may not provide an accurate or complete picture. Azzarito, Solmon, and Harrison (2006) concluded that the high school-aged girls in their study participated actively in physical education classes. This finding was consistent with earlier studies (see Flintoff and Scraton 2001;Williams and Bedward 2001).…”
Section: Introductionmentioning
confidence: 97%